OPTIMASI DAN UJI AKTIFITAS ANTIOKSIDAN FORMULA TONER MINYAK DAUN SIRIH HIJAU (Piper betle L.) - Nesa Agistia; Benni Iskandar; Nofriyanti Nofriyanti (Universitas Lambung Mangkurat, 2026)
Exposure to free radicals can damage the skin. Green betel leaf oil, which has antioxidant activity, can be formulated into a toner. This study aimed to determine the optimal toner formula and Â to evaluate its antioxidant activity. Optimization was performed using a factorial design with two factors: Tween 80 and PEG 400 concentrations. The optimum formula, determined with Design Expert 13, consisted of 10% Tween 80 and 5% PEG 400, with a predicted pH of 5.66 and 99% transmittance. Validation using a One-Sample T-Test showed no significant difference (p > 0.05) between the predicted and actual results. The optimized toner had a pH of 5.69, a transmittance of 99.2%, a particle size of 12.2 nm, and very strong antioxidant activity (IC50 = 43.29 Âµg/mL). In this research, an optimum toner formula was obtained which has good physical properties and very strong antioxidant activity.Â